Analisys of Lead content in Tilapia (Oreochromis niloticus) from Taliwang Lake - Khairuddin, Khairuddin; Yamin, M.; Kusmiyati, Kusmiyati; Sedijani, Prapti (Jurnal Biologi Tropis, 2025)
Research on heavy metals is important to be done to protect consumers from dangerous impact especially on human beings. The purpose of this study was to determine the Lead (Pb) content in Tilapia (Oreochromis niloticus) taken from Rawa Taliwang Lake. Specifically, the benefit of this study is to protect consumers who consume Tilapia from Lead heavy metal contaminants. Data collection for the tilapia species in this study was carried out in water bodies within the Taliwang Lake area. There were 2 data collection stations, namely on the east and west sides of the lake. Gill nets were used to catch tilapia. Fish samples were caught as many as 4 fish for each station. Next, each fish sample was put into a plastic bag and then stored in a sample box. The fish samples were then analyzed at the West Nusa Tenggara Health, Testing and Calibration Laboratory Center. The data analysis method was carried out by taking muscle tissue from the fish and then analyzing the Pb heavy metal content using an Atomic Absorption Spectrophotometer. The concentration of Lead in fish tissue was measured after adding concentrated Na2SO4 and CuSO4, which were heated at 350ºC for 2-3 hours until the solution was clear. The conclusion of this study is that the heavy metal content of Pb in Tilapia (Oreochromis niloticus) is <0.5 ppm.